The Effect of Learning Style Differentiated Learning on Learning Outcomes and Motivation of Grade IV Learners in Mathematics Subjects: Differentiated Learning Styles' Impact on Math Achievement and Motivation - Komarudin Komarudin; Dya Ayu Agustiana Putri (Primary Education Insight, 2025)
The uniqueness of each learner's learning style, whether visual, auditory, or kinesthetic, demands teacher attention. By fulfilling diverse learning needs, learners feel more valued, spurring learning outcomes and motivation. This research examines the impact of differentiated learning styles on IV-grade students' mathematics performance and motivation. An approach focused on quantifiable data utilizing a posttest-only control group design was employed in this study. A total of 31 learners, divided into control and experimental groups, were tested. Data were collected through administering tests and questionnaires. The findings of the study showed a striking difference. The control class had an average learning outcome of 66 and an average motivation of 65.1, while the experimental class achieved an average learning outcome of 92.5 and an average motivation of 86.1. The hypothesis analysis conducted using Jamovi 2.3.28 confirmed this difference, showing a p-value of < 0.001 in both multivariate tests (including Pillai's Trace, Wilks' Lambda, Hotelling's Trace, and Roy's Largest Root) and univariate tests with the same significance level. These findings suggest that differentiated learning enhances student outcomes and motivation.